Urease Expression in Pathogenic Yersinia enterocolitica Strains of Bio-Serotypes 2/O:9 and 1B/O:8 Is Differentially Regulated by the OmpR Regulator - Nieckarz, Marta; Kaczor, Patrycja; Jaworska, Karolina; Raczkowska, Adrianna; Brzostek, Katarzyna (Frontiers in Microbiology, 2020)
Yersinia enterocolitica exhibits a dual lifestyle, existing as both a saprophyte and a pathogen colonizing different niches within a host organism. OmpR has been recognized as a regulator that controls the expression of genes involved in many different cellular processes and the virulence of pathogenic bacteria. Here, we have examined the influence of OmpR and varying temperature (26°C vs. 37°C) on the cytoplasmic proteome of Y. enterocolitica Ye9N (bio-serotype 2/O:9, low pathogenicity). Differential label-free quantitative proteomic analysis indicated that OmpR affects the cellular abundance of a number of proteins including subunits of urease, an enzyme that plays a significant role in acid tolerance and the pathogenicity of Y. enterocolitica. The impact of OmpR on the expression of urease under different growth conditions was studied in more detail by comparing urease activity and the transcription of ure genes in Y. enterocolitica strains Ye9N and Ye8N (highly pathogenic bio-serotype 1B/O:8). Urease expression was higher in strain Ye9N than in Ye8N and in cells grown at 26°C compared to 37°C. However, low pH, high osmolarity and the presence of urea did not have a clear effect on urease expression in either strain. Further analysis showed that OmpR participates in the positive regulation of three transcriptional units encoding the multi-subunit urease (ureABC, ureEF and ureGD) in strain Ye9N, but this was not the case in strain Ye8N. Binding of OmpR to the ureABC and ureEF promoter regions was confirmed using an electrophoretic mobility shift assay, suggesting that this factor plays a direct role in regulating the transcription of these operons. In addition, we determined that OmpR modulates the expression of a ureR-like gene encoding a putative regulator of the ure gene cluster, but in the opposite manner, i.e. positively in Ye9N and negatively in Ye8N. These findings provide some novel insights into the function of OmpR in adaptation strategies of Y. enterocolitica.